Analysis of the Influence of Socioeconomic Status on Smartphone Use Restrictions in Early Childhood: A Digital Parenting Survey Study - Desni Yuniarni (Jurnal Pedagogi dan Pembelajaran, 2026)
Parents’ socioeconomic status (SES) is a key factor influencing how they regulate and supervise young children’s smartphone use. This study aimed to analyze differences in parental restriction methods based on SES. Using a quantitative cross-sectional design, data were collected from 115 parents of children aged 3–6 years enrolled in kindergartens and early childhood education centers (TK/PAUD) through purposive sampling. Inclusion criteria required that the child had used a smartphone for at least six months. Data were gathered online via Google Forms and analyzed using the Chi-square test to examine associations between SES categories and restriction methods. The results showed that conventional restriction methods were more commonly applied than digital ones across all education and occupation groups. Chi-square analysis indicated significant differences between SES and the restriction methods employed. Parents with higher SES tended to use digital features such as parental control and screen time monitoring, whereas those with lower SES relied on direct communication and physical supervision. These findings highlight that SES significantly shapes parental strategies for regulating children’s smartphone use and emphasize the importance of inclusive digital literacy programs to support effective and adaptive digital parenting practices.